Elemety marketingu w gminie - Marks, Małgorzata (Marketing Components in Local Community, 2006)
The aim of this study is to present some theoretical definitions of place marketing. The author also shows short conclusions connected with the implementation of classical marketing in local community management.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1124, s. 375-381